Clinical focus. Effects of intensive voice treatment (the Lee Silverman Voice Treatment [LSVT]) on ataxic dysarthria: a case study [corrected] [published erratum appears in AM J SPEECH LANG PATHOL 2004 Feb;13(1):93]. - Sapir S; Spielman J; Ramig LO; Hinds SL; Countryman S; Fox C; Story B (American Journal of Speech-Language Pathology, 2003)
This study examined the effects of intensive voice treatment (the Lee Silverman Voice Treatment [LSVT]) on ataxic dysarthria in a woman with cerebellar dysfunction secondary to thiamine deficiency. Perceptual and acoustic measures were made on speech samples recorded just before the LSVT program was administered, immediately after it was administered, and at 9 months follow-up. Results indicate short- and long-term improvement in phonatory and articulatory functions, speech intelligibility, and overall communication and job-related activity following LSVT. This study's findings provide initial support for the application of LSVT to the treatment of speech disorders accompanying ataxic dysarthria. Potential neural mechanisms that may underlie the effects of loud phonation and LSVT are addressed.